(untitled) (University of Khartoum Engineering Journal, 2022)
This paper shows the difference in video quality between two compressed videos using H.264 AVC (Advanced Video Coding) and H.265 HEVC (High Efficiency Video Coding) encoders. To evaluate video completely it should be prepared video files that have a variety of bit rates and content. There are many video quality assessment methods. We can divide the min to subjective and objective methods. Subjective are conducted by a human perception and objective are conducted by a computer software which is calculating the video quality. All of these methods have theirs advantages and disadvantages. To generate compressed videos from the original video FFmpeg (Fast Forward-moving picture experts group) converter has been used. MSU-VQMT (Moscow State University’s Video Quality Measure- mentTool) was used to perform comparative objective analysis of video quality. Delta, MSE (mean square Error), MSAD (Mean Sum of Absolute Difference), PSNR (Peak Signal-to-Noise Ratio), and SSIM (Structural Similarity Index Measure) metrics were measured. The result from FFmpeg shows that the size of the compressed video using the H.265 codec has been decreased by 50% compared to the compressed video using the H.264 codec. The comparison of metrics shows that delta, MSAD, PSNR, and SSIM values of H.265 encoded video was decreased, while Delta and MSE value was increased compared to H.264 encoded Video. That’s mean the overall video quality was decreased but the video size was enhanced.